2010
DOI: 10.4103/0019-5049.71037
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for lower-segment caesarean section: Changing perspectives

Abstract: The number of caesarean sections has increased over the last two decades, especially in the developed countries. Hence, it has increasingly become a greater challenge to provide care for the parturient, but this has given obstetric anaesthetists a greater opportunity to contribute to obstetric services. While caesarean deliveries were historically performed using general anaesthesia, there is a recent significant move towards regional anaesthesia. Unique problems that patients with obesity and pre-eclampsia pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 40 publications
0
24
0
1
Order By: Relevance
“…29 Obstretics patients undergoing caesarean section under general anaesthesia require rapid sequence induction and intubation (RSII) due to the high risk of aspiration. High rates of caesarean section surgeries are encountered by anaesthesiologists now a days.…”
Section: Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…29 Obstretics patients undergoing caesarean section under general anaesthesia require rapid sequence induction and intubation (RSII) due to the high risk of aspiration. High rates of caesarean section surgeries are encountered by anaesthesiologists now a days.…”
Section: Introduction:-mentioning
confidence: 99%
“…Because the airway is unprotected during this time, it is the most critical period during which aspiration of gastric contents is likely to occur. 29 The depolarizing neuromuscular blocking agent, succinylcholine has been the drug of choice for rapid sequence induction and intubation (RSII) and anticipated difficult intubations for its short and rapid acting properties. Nothing had yet replaced succinylcholine in the scenarios of difficult intubation before yet, with advent of Rocuronium antagoinist (ORG-25969, sugamedax) that chelates the drug and act as the reversal agent, Rocuronium can also be used in difficult intubation situations in RSII.…”
Section: Introduction:-mentioning
confidence: 99%
“…Recently, researchers have suggested that rocuronium-sugammadex combination may replace succinylcholine in the near future 10,11 . Sugammadex, a selective relaxant-binding agent, antagonizes the effects induced by rocuronium on muscle tissue and quickly resolves neuromuscular blockade.…”
Section: Intravenous Induction Agentsmentioning
confidence: 99%
“…4 This increase is seen more in primigravidae compared to multigravida which compromises their obstetric future in the form of vaginal delivery, as patients who have undergone caesarean section once are less likely to opt for vaginal birth after caesarean (VBAC) as clinicians and patients are not ready to take risk of scar rupture and high perinatal mortality. 5 This results in exponential increase in CS.…”
Section: Introductionmentioning
confidence: 99%